Artificial Intelligence in Design Process: An Analysis Using Text Mining - Younjung Hwang; Seokjun Jeong; Yi Wu (Applied Artificial Intelligence)
The progress of Artificial Intelligence (AI) offers modern designers opportunities to explore innovative design processes. Particularly, generative AI that creates images and other content through text can contribute to the creative processes in various design fields such as graphics, industrial design, UX, and fashion. However, there is a lack of comprehensive research on AI’s role and applications throughout the entire design process, and current papers often employ qualitative methods such as interviews and case studies. Therefore, this paper aims to quantitatively analyze experts’ views on AI’s utilization in the whole design process through text mining of literature. The researchers selected 126 papers through scientific databases such as ScienceDirect, Web of Science, and utilized the keyword matching method to extract the frequency of keywords for each stage of the design process – Research, Ideation, Mock-up, Production, and Evaluation. Through text mining, research findings indicate that AI is predominantly discussed in the later stages of design, particularly in the production process, while its use in the mock-up stage is perceived to be low. Additionally, distinct differences in AI use across design disciplines were identified: graphics focusing on ideation; UX on evaluation; and fashion on production.